Numerical optimization of topological photonic waveguides - Chan, Ric (Nanyang Technological University, 2024)
The integration of topological concepts from condensed matter physics into photonics has sparked a new era of innovation in the design of photonic waveguides. These topological photonic waveguides offer a unique solution for efficiently routing light around corners while minimizing backscattering losses. They have found applications across various platforms, including “on-chip" configurations, making them ideal for integrated optical systems.